2009
DOI: 10.1021/jp904728n
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Resolved Laser-Induced Breakdown Spectroscopy of Al

Abstract: It is shown that the continuous background of the laser-induced breakdown spectrum of Al produced by 800 nm femtosecond pulses is strongly polarized. Use of a polarizer to filter out the background significantly improves the signal/noise and signal/background ratios of the discrete line spectrum. The effects of the laser pulse energy, focal position, incidence and detection angles, and the polarization plane of the laser were investigated. Polarization resolved laser-induced breakdown spectroscopy (PRLIBS) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Another way to deduct a continuous background is to add a polarizer to the collected light path. Penczak et al's [26] research results show that the continuous background of the Al plasma emission spectra induced by 800 nm femtosecond pulse laser is strongly polarized. The use of a polarizer can effectively filter the continuous spectrum, thus improving the signal-to-noise ratio and the signal-to-back ratio of the characteristic spectrum.…”
Section: Correction and Removal Of Continuum Backgroundmentioning
confidence: 98%
“…Another way to deduct a continuous background is to add a polarizer to the collected light path. Penczak et al's [26] research results show that the continuous background of the Al plasma emission spectra induced by 800 nm femtosecond pulse laser is strongly polarized. The use of a polarizer can effectively filter the continuous spectrum, thus improving the signal-to-noise ratio and the signal-to-back ratio of the characteristic spectrum.…”
Section: Correction and Removal Of Continuum Backgroundmentioning
confidence: 98%
“…7 of Ref. [3]). We also found that the laser-induced breakdown spectrum (LIBS) of air is likewise unpolarized (unpublished data associated with Ref.…”
mentioning
confidence: 88%
“…Light emitted by the excited material can provide valuable information about the ablation mechanism as well as a powerful tool for analyzing the elemental composition of the substrate. A number of studies have shown that the light emitted from laser-induced plasmas, especially the continuum radiation, can be strongly polarized [1][2][3][4][5]. This effect was observed for a wide variety of solid materials and for both nanosecond and femtosecond excitation.…”
mentioning
confidence: 99%
“…The technique of PPS has been applied to laser produced plasmas where partial polarisation has been observed in the x-ray and visible spectral ranges [2,3]. Importantly, a particular application of PPS known as polarisation-resolved laser induced breakdown spectroscopy (PRLIBS) exploits this partial polarisation in order to enhance the signal to background ratio over traditional LIBS measurements [4]. In various wide-ranging studies [4][5][6], it was shown that the continuum radiation tends to have a greater degree of polarisation than the line emission.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a particular application of PPS known as polarisation-resolved laser induced breakdown spectroscopy (PRLIBS) exploits this partial polarisation in order to enhance the signal to background ratio over traditional LIBS measurements [4]. In various wide-ranging studies [4][5][6], it was shown that the continuum radiation tends to have a greater degree of polarisation than the line emission. For this reason, placing a polariser in front of a spectrometer results in lower background continuum, thus increasing the signal-background ratio which is a figure of merit for LIBS.…”
Section: Introductionmentioning
confidence: 99%